The writing is on the wall: Medical students express their views and anguish - L.J. Mathibe (South African Family Practice)
Students often write messages on toilet walls. Some of these messages are derogatory, but some express their anguish, and reflect the challenges that they face while training. In this brief report, three messages, chosen from many which were written on public bathroom walls by medical students at one of the universities in South Africa, were analysed. A story of one brave medical student is also narrated. She chose not to express her emotions and ask for help, in the same way that many of her peers did.